Adobe InDesign classroom in a book (2023 release) : the official training workbook from Adobe - Anton, Kelly Kordes; DeJarld, Tina (Classroom in a book., 2023)
Learn graphic design using Adobe InDesign Adobe InDesign Classroom in a Book (2023 release) uses real-world, project-based learning to cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. For beginners and experienced users alike, you can follow the book from start to finish or choose only those lessons that interest you. Learn to: Build a strong foundation of typographic, page layout, and document-construction skills Handle images from Adobe Photoshop and line drawings from Adobe Illustrator Create effects with layers and transparency Bring messages to life with beautiful typography and color Export work for professional printing, websites, social media, eBooks, and more Classroom in a Book℗ʼ, the best-selling series of hands-on software training workbooks, offers what no other book or training program doesan official training series from Adobe, developed with the support of Adobe product experts. Purchasing this book includes valuable online extras. Follow the instructions in the book's "Getting Started" section to unlock access to: Downloadable lesson files you need to work through the projects in the book Web Edition containing the complete text of the book, interactive quizzes, and videos that walk you through the lessons step by step What you need to use this book: Adobe InDesign (2023 release) software, for either Windows or macOS. (Software not included.) Note: Classroom in a Book does not replace the documentation, support, updates, or any other benefits of being a registered owner of Adobe InDesign software.